Vitamin K deficiency bleeding in children with cholestatic liver disease: a systematic review and meta-analysis - Anusak Sakwit; Pongpak Pongphitcha; Patcharee Komvilaisak; Masayuki Ochiai; Daijiro Takahashi; Shutaro Suga; Ampaiwan Chuansumrit; Marisol Betensky; Stephen P. Pereira; Amber Afzal; C. Heleen van Ommen; Neil Goldenberg; et al. (Research and Practice in Thrombosis and Haemostasis)
Vitamin K deficiency (VKD) in cholestatic liver disease affects up to 23% of pediatric patients. While several vitamin K (VK) prophylaxis regimens have been proposed, optimal therapeutic strategies remain undefined. The study aimed to identify the most effective VK prophylaxis for children with cholestatic liver disease. We conducted a systematic review of articles focusing on studies of children aged <18 years with cholestatic liver disease who reported outcomes of either VKD or vitamin K deficiency bleeding (VKDB) after VK prophylaxis. The articles were sourced from PubMed, Scopus, and Embase. A meta-analysis was performed to determine the prevalence of VKD and the efficacy of each prophylactic protocol in preventing VKD/VKDB. The study was registered on PROSPERO (CRD 42021270048). Of the 889 articles, 37 were selected (2 comparative studies, 6 noncomparative studies, and 29 case reports/series). The results from the comparative studies indicated a lower incidence of VKD in the parenteral than that in the oral VK. The meta-analysis of the noncomparative studies showed the prevalence of VKD in high prothrombin induced by vitamin K absence-II group was 56% (95% CI, 45%-68%; I2 = 0.0%; H2 = 1.0; Q test: χ2 = 1.93; P = .38) and a prevalence of VKD in abnormal coagulation test was 10% (95% CI, 5%-14%; I2 = 0%, H2 = 1.0; Q test: χ2 = 0.82; P = .66), respectively. Among the 3 administrative routes, the analysis from case reports/series showed the median onset of VKDB in cholestatic infants was the earliest in the oral (44.5 days; IQR, 13.0-240.0 days) compared with intramuscular (86.0 days; IQR, 36.0-120.0) and intravenous routes and intravenous (97.0 days; IQR, 74.0-120.0 days) VK prophylaxis. Available studies to determine the optimal route of VK administration in children with cholestatic liver disease were limited. The result from the review indicated that parenteral VK demonstrated a noticeable advantage over oral VK for VKD/VKDB prevention in cholestatic children.